2022
DOI: 10.1007/s00267-022-01732-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Anthropogenic VOCs Emission Based on Volatile Chemical Products: A Canadian Perspective

Abstract: Volatile organic compounds (VOCs) in urban areas are of great interest due to their significant role in forming ground-level ozone and adverse public health effects. Emission inventories usually compile the outdoor VOCs emission sources (e.g., traffic and industrial emissions). However, considering emissions from volatile chemical products (e.g., solvents, printing ink, personal care products) is challenging because of scattered data and the lack of an effective method to estimate the VOCs emission rate from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Examination of indoor emissions of VOCs by sampling residences in Canada, China, and the U.S.A., indicated that the following highest concentration levels were limonene, toluene, m-p xylene, α-pinene, pentane, and decane (Canada and the U.S.A.), and toluene, naphthalene, ethyl-acetate, and m-p-xylene (China). In such a study, the indoor VOCs’ fluctuation and levels are linked to building microenvironments and age, the frequency of product consumption, and ventilation conditions, among other factors [ 46 ].…”
Section: Volatile Organic Compounds In Fragranced Productsmentioning
confidence: 99%
“…Examination of indoor emissions of VOCs by sampling residences in Canada, China, and the U.S.A., indicated that the following highest concentration levels were limonene, toluene, m-p xylene, α-pinene, pentane, and decane (Canada and the U.S.A.), and toluene, naphthalene, ethyl-acetate, and m-p-xylene (China). In such a study, the indoor VOCs’ fluctuation and levels are linked to building microenvironments and age, the frequency of product consumption, and ventilation conditions, among other factors [ 46 ].…”
Section: Volatile Organic Compounds In Fragranced Productsmentioning
confidence: 99%
“…Canadian cities also generally have lower pollutant levels, and less-regulated sources, such as VCPs, could contribute a more significant fraction of air pollutants. Asif et al conducted a literature review on studies targeting VOC emissions in Canada between 2000 and 2022 and identified paints and solvents as crucial emerging sources . They suggested future studies to consider building detailed emission inventories, especially for household products such as cleaners and personal care products.…”
Section: Introductionmentioning
confidence: 99%
“…Asif et al conducted a literature review on studies targeting VOC emissions in Canada between 2000 and 2022 and identified paints and solvents as crucial emerging sources. 14 They suggested future studies to consider building detailed emission inventories, especially for household products such as cleaners and personal care products. This work analyzed the effect of indoor physicochemical phenomena on VCP emissions utilizing an established bottomup approach 8 to build a VCP emission inventory for Canada, followed by chemical speciation and allocation of emissions to indoor and outdoor premises.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Today, environmental management is developing primar ily with the practical solution of environmental problems re lated to the production and consumption of goods and servic es. The "agenda of the 21 st century", adopted in Rio de Ja neiro in 1992, indicates that it is necessary to attribute "envi ronmental management" to the dominant rock of sustainable development and, at the same time, to the high priority of in dustrial activity and entrepreneurship [7].…”
mentioning
confidence: 99%
“…The purpose of Environmental Management is to improve management in the field of Environmental Protec tion, assess and reduce risks associated with the use of raw ma terials and materials, optimize the use of Natural Resources, assess the compliance of the enterprise's activities with current legislation, develop priority measures and longterm policies in solving environmental problems (Fig. 1) [7,8].…”
mentioning
confidence: 99%